T2T || FAQ || Ask T2T || Teachers' Lounge || Browse || Search || Thanks || About T2T
View entire discussion
Sorry it has taken me so long to reply, but I couldn't locate the proof you wanted until today! Start off with a = b then multiply by a a^2 = ab subtract b^2 a^2 - b^2 = ab - b^2 factor (a+b)(a-b) = b(a-b) divide (a-b) a + b = b substitute b + b = b simplify 2b = b divide by b 2 = 1 Of course there are errors in the process that allow for division by zero (a- b) since a = b.
Math Forum Home || The Math Library || Quick Reference || Math Forum Search